Secondary predicates (depictives) - Čižik-Prokaševa, Veslava (Lietuvių kalba, 2010)
The paper sets out to investigate the notion of predicates. It also offers an overview of their classification in Lithuanian and foreign linguistics. Most attention is given to free secondary predicates (predicative adjuncts), focusing on predicates with no resultative meaning, i.e. depictives. A secondary predicate is a word syntactically dependent on the main verb (in cases of complementation it is also semantically dependent) and semantically related to its argument. It refers to primary or secondary predication of the clause. According to the character of the syntactic relation, a distinction is made between predicative complements (the predicative is governed by the verb) and predicative adjuncts (the predicative modifies the verb). According to meaning, two types of secondary predicates are divided into non-resultative and resultative. Free non-resultative predicates are by some linguists referred to as depictives (in a general meaning) and by others as depictives (in a narrow sense) and circumstantial secondary predicates.In Lithuanian depictives usually agree with the verbal argument (depictives in concord); however, there are depictives which only partially agree with the verb argument (in number, gender) or do not agree altogether (semantic depictives).